Real-world adherence to non-vitamin K antagonist oral anticoagulants in patients with atrial fibrillation measured by an electronic medication event monitoring system. (25th November 2020) - Delesie, M; Knaepen, L; Adam, B; Dendale, P; Vijgen, J; Ector, J; Desteghe, L; Heidbuchel, H
Abstract: Background: Non-vitamin K antagonist oral anticoagulants (NOACs) are recommended as first choice therapy for thrombo-embolic prevention in patients with non-valvular atrial fibrillation (AF) and an elevated CHA2DS2-VASc score. A critical determinant for both safety and effectiveness of NOAC treatment is adherence to the prescribed medication regimen. Real-life adherence is suboptimal for many cardiovascular drugs. Measuring and improving NOAC adherence is primordial for optimising AF care. Purpose: We measured adherence to any of the four NOACs in a population of AF patients who participate to a clinical trial during which they received targeted education on AF and its treatment. Methods: This analysis is part of a prospective, multicenter, randomized controlled trial which is currently ongoing at three Belgian hospitals (AF-EduCare study). Ambulatory or hospitalised AF patients of that trial, treated with a NOAC, and who received a short targeted education session about AF and NOAC therapy at initiation, form the study group of this analysis. Monitoring of NOAC intake was performed by an electronic Medication Event Monitoring System (MEMS), starting immediately after initiation of the study and the education session (for 3 months). A special cap fits on a medication bottle and records the exact date and time of bottle openings. An LCD screen on the cap displays the number of openings of the medication bottle over a period of 24 hours, providing feedback about the correct intake. Dabigatran was replaced by a proxy medication as Dabigatran should be stored in the original package in order to protect it from moisture. Regimen adherence was calculated as the number of days on which one bottle opening in case of Rivaroxaban or Edoxaban and two bottle openings in case of Apixaban or Dabigatran is/are registered, divided by the total number of monitored days and multiplied by 100. Results: A total of 233 patients (mean age 71.0±7.7 years; 71.2% males; CHA2DS2-VASc score 3.4±1.5; mean duration of AF history 5.8±7.5 years) were given a MEMS. Of these patients 32.2%, 31.3%, 26.2% and 10.3% were respectively on Edoxaban, Apixaban, Rivaroxaban and Dabigatran. Regimen adherence for these NOACs was 95.9±9.3%, 91.6±13.7%, 95.6±5.6% and 94.0±7.1% respectively. Overall, 94.4% of the patients had an adherence >80% and 81.1% had an adherence >90%. Adherence for the once and twice daily regimens was 95.8±0.7% and 92.2±1.3%, respectively (p=0.0003; Mann-Whitney U test). Conclusions: This is a first prospective study investigating adherence for all NOACs using electronic monitoring. In this sample of AF patients who underwent a targeted education session before the 3 month monitoring period, mean adherence to NOAC intake was >90% for all NOACS. This high adherence may be related to both the education and the use of MEMS, which provided direct feedback to the patient. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): The AF-EduCare study is a project supported by the Fund for Scientific Research, Flanders (T002917N).